The Role of Convalescent Plasma and Tocilizumab in the Management of COVID-19 Infection: A Cohort of 110 Patients from a Tertiary Care Hospital in Oman - Faryal Khamis; Ziad Memish; Maher Al Bahrani; Hamed Al Nummani; Dana Al Raisi; Samata Al Dowaiki; Shabnam Chhetri; Fatma Al Fahdi; Maha Al Yahyai; Nenad Pandak; Zakariya Al Bolushi; Zainab Alarimi; et al. (Springer, 2021)
Aim: As Coronavirus Disease-2019 (COVID-19) pandemic continues to evolve, the search for safe and effective therapeutic interventions remain essential. Methods: We conducted a retrospective cohort study on patients hospitalized with laboratory confirmed severe acute respiratory syndrome coronavirus-2 infection, comparing standard of care along with Convalescent Plasma with or without Tocilizumab (CP vs. CPT). Results: A total of 110 patients were enrolled with an overall mean age of 50 ± 16 years. Patients on CPT were more likely to have had acute respiratory distress syndrome (77% vs. 42%; p < 0.001), sepsis (9.7% vs. 0; p = 0.036), chest X-ray abnormalities (71% vs. 44%; p = 0.004), intensive care unit admission (84% vs. 56%; p = 0.001) as well as being on mechanical ventilation (79% vs. 48%; p = 0.001). After CPT treatment, all measured inflammatory markers, except interleukine-6, showed an overall steady decline over time (all p-values <0.05) and the ventilatory parameters showed significant improvement of PaO2/FiO2 ratio from 127 to 188 within 7 days (p < 0.001). Additionally, 52% (32/62) of the patients had favorable outcome, either as improvement of ventilatory parameters or extubation within 14 days of hospitalization. However, mortality rate in those on CPT was higher than those who received CP alone (24% vs. 8.3%; p = 0.041). Conclusion: In patients with severe COVID-19 infection, using tocilizumab with convalescent plasma is associated with improvement in inflammatory and ventilatory parameters but no effect on mortality. These findings require validation from randomized clinical trials.